Did adhering to the gold standard reduce the cost of capital? - Ron Alquist; Ben Chabot (Federal Reserve Bank of Chicago, 2010)
A commonly cited benefit of the pre-World War One gold standard is that it reduced the cost of international borrowing by signaling a country's commitment to financial probity. Using a newly constructed data set that consists of more than 55,000 monthly sovereign bond returns, we test if gold-standard adherence was negatively correlated with the cost of capital. Conditional on UK risk factors, we find no evidence that the bonds issued by countries off gold earned systematically higher excess returns than the bonds issued by countries on gold. Our results are robust to allowing betas to differ across bonds issued by countries off-and on-gold; to including proxies that capture the effect of fiscal, monetary, and trade shocks on the commitment to gold; and to controlling for the effect of membership in the British Empire.
Keywords: F33; G15; N23; 330; gold standard; sovereign borrowing costs; country risk premium